2008
DOI: 10.1128/aem.00468-08
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of an Escherichia coli Strain for the Production of 3-Methyl-1-Butanol

Abstract: 3-Methyl-1-butanol is a potential fuel additive or substitute. Previously this compound was identified in small quantities in yeast fermentation as one of the fusel alcohols. In this work, we engineered an Escherichia coli strain to produce 3-methyl-1-butanol from glucose via the host's amino acid biosynthetic pathways. Strain improvement with the removal of feedback inhibition and competing pathways increased the selectivity and productivity of 3-methyl-1-butanol. This work demonstrates the feasibility of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 17 publications
(16 reference statements)
0
108
0
Order By: Relevance
“…In addition to n-butanol, E. coli has also recently been engineered for the 570 production of other potential biofuels consisting of higher alcohols such as iso-butanol 571 (Atsumi et al, 2008b), 2-methyl-1-butanol (Cann and Liao, 2008), 3-methyl-1-butanol 572 (Connor and Liao, 2008), as well as n-pentanol, 3-methyl-1-pentanol, and n-hexanol 573 (Zhang et al, 2008b). Despite their favorable thermodynamic properties, it has been 574 thoroughly demonstrated that the cytotoxicity of an alcohol is elevated with an increasing 575 carbon chain length (Heipieper and Debont, 1994;Osborne et al, 1990a;Vermue et al, 576 1993).…”
mentioning
confidence: 99%
“…In addition to n-butanol, E. coli has also recently been engineered for the 570 production of other potential biofuels consisting of higher alcohols such as iso-butanol 571 (Atsumi et al, 2008b), 2-methyl-1-butanol (Cann and Liao, 2008), 3-methyl-1-butanol 572 (Connor and Liao, 2008), as well as n-pentanol, 3-methyl-1-pentanol, and n-hexanol 573 (Zhang et al, 2008b). Despite their favorable thermodynamic properties, it has been 574 thoroughly demonstrated that the cytotoxicity of an alcohol is elevated with an increasing 575 carbon chain length (Heipieper and Debont, 1994;Osborne et al, 1990a;Vermue et al, 576 1993).…”
mentioning
confidence: 99%
“…Continuing with the theme of using amino acid biosynthetic pathways to produce higher alcohols, Connor and Liao [20] improved the production of 3MB, a C 5 alcohol with an energy density of 30.5 MJ/L close to that of gasoline (32 MJ/L). The production of 3MB builds onto previous work by Atsumi et al [17] to produce isobutanol from 2-ketoisovalerate.…”
Section: Re-routing Of the Amino Acid Biosynthetic Pathway For Producmentioning
confidence: 99%
“…Clostriduim were recently expressed in E. coli. Aside from producing ethanol during fermentation, S. cerevisiae is also known to produce higher alcohols and esters from amino acids [19][20][21]. Recently, a similar pathway for higher alcohol production was expressed in E. coli to yield six different straight and branched-chain alcohols, and the same group has demonstrated production of 1.28 g/L of isopentanol by increasing the flux through the desired pathway [ 22].…”
Section: Production Hostmentioning
confidence: 99%